Impact forces and torques transmitted to the hand by tennis racquets - Cross, R. (Sports Technology, 2010)
When a tennis racquet is used to strike a ball, impulsive and vibration forces are transmitted to the hand and arm. Measurements are presented showing that the dynamics of the collision can be described by replacing the hand and arm with a mass of about 200 g attached rigidly to the end of the handle. This information was combined with a flexible beam model of a racquet to calculate the impulsive and vibration forces on the hand as functions of various physical properties of the racquet, for impacts along the longitudinal axis of the racquet face. The force on the hand is largest for impacts near the tip or throat of the racquet and is a smallest for impacts near the middle of the strings. It is shown that the force can be reduced by using a heavier or stiffer racquet, by increasing the mass of the head rather than the handle, or by using softer strings or softer balls.